Competitive success of southern populations of Betula pendula and Sorbus aucuparia under simulated southern climate experiment in the subarctic - Taulavuori K; Taulavuori E; Saravesi K; Jylanki T; Kainulainen A; Pajala J; Markkola A; Suominen O; Saikkonen K (WILEY, 2022)
Global warming has been commonly accepted to facilitate species' range shifts across latitudes. Cross-latitudinal transplantations support this; many tree species can well adapt to new geographical areas. However, these studies fail to capture species' adaptations to new light environment because the experiments were not designed to explicitly separate species' responses to light and temperature. Here we tested reaction norms of tree seedlings in reciprocal transplantations 1,000km apart from each other at two latitudes (60 degrees N and 69 degrees N). In contrast to past studies, we exposed our experimental plants to same temperature in both sites (temperature of 60 degrees N growing site is recorded to adjust temperature of 69 degrees N site in real time via Internet connection) while light environment (photoperiod, light quality) remained ambient. Shoot elongation and autumn coloration were studied in seedlings of two deciduous trees (Betula pendula and Sorbus aucuparia), which were expected to respond differently to day length. Sorbus as a member of Rosaceae family was assumed to be indifferent to photoperiod, while Betula responds strongly to day length. We hypothesized that (1) southern and northern populations of both species perform differently; (2) southern populations perform better in both sites; (3) autumn phenology of southern populations may delay in the northern site; (4) and Sorbus aucuparia is less dependent on light environment. According to the hypotheses, shoot elongation of northern population was inherently low in both species. An evolutionary consequence of this may be a competitive success of southern populations under warming climate. Southern population of B.pendula was delayed in autumn coloration, but not in growth cessation. Sorbus aucuparia was less responsive to light environment. The results suggest that light provides selection pressure in range shifts, but the response is species dependent.